1941
DOI: 10.1785/bssa0310030187
|View full text |Cite
|
Sign up to set email alerts
|

A contribution to the seismic history of Missouri*

Abstract: The status of Missouri as a state which contains active seismic areas has been a subject for speculation ever since the New Madrid earthquakes of 1811 and 1812. Local seismic research, however, was slow in starting, owing principally to the lack of available instruments to supply data sufficiently accurate for detailed work. Two events which gave great impetus to the progress of Missouri earthquake study were, first, the installation of the seismograph at St. Louis University in 1909, and second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1946
1946
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…data, 1980). Reports of damage include fallen chimneys and cracked brick walls at Memphis (Heinrich, 1941); damaged chimneys at Covington, Jackson, and Nashville in Tennessee, at Helena in Arkansas, at Mills Point [now Hickman] in Kentucky, and at New Madrid and Saint Louis in Missouri. In the St. Francis River area of northeastern Arkansas a hunter reported that a deep lake had been formed by the earth's sinking on the river.…”
Section: New Madrid Poplar Bluffmentioning
confidence: 99%
See 4 more Smart Citations
“…data, 1980). Reports of damage include fallen chimneys and cracked brick walls at Memphis (Heinrich, 1941); damaged chimneys at Covington, Jackson, and Nashville in Tennessee, at Helena in Arkansas, at Mills Point [now Hickman] in Kentucky, and at New Madrid and Saint Louis in Missouri. In the St. Francis River area of northeastern Arkansas a hunter reported that a deep lake had been formed by the earth's sinking on the river.…”
Section: New Madrid Poplar Bluffmentioning
confidence: 99%
“…intensity is at least VIII, and probably IX; VIII is assigned at seven places by Hopper and Algermissen (1980). Heinrich (1941) notes that at Charleston "every building in the commercial block was damaged...and many walls were cracked." At Cairo "the number of chimneys shaken down in the city probably runs into the hundreds" (Marvin, 1895).…”
Section: Saint Louis Missourimentioning
confidence: 99%
See 3 more Smart Citations